Increased rate of multidrug-resistant gram-negative bacterial infections in hospitalized immunocompromised pediatric patients - Sarah Khafaja; Sarah Khafaja; Yara Salameh; Celina F. Boutros; Cherine Awad; Kawthar Faour; Nadim Tfaily; Sarah Merhi; Zeinab El Zein; Zeinab El Zein; Samer Bou Karroum; Dana Oweini; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionMultidrug resistant Gram-negative bacterial infections are considered a major public health threat. Immunocompromised pediatric patients are at a great risk of severe or overwhelming infections. The aim of this study was to describe the frequency of infections with multidrug resistant (MDR) Gram-negative bacteria (GNB) in immunocompromised pediatric patients and to determine the risk factors. In addition, we aimed to identify the antimicrobial resistance patterns of these isolates.Materials and methodsThis was a retrospective observational study conducted at the American University of Beirut Medical Center (AUBMC) from 2009 to 2017. The study included immunocompromised patients 18 years of age or younger with infections caused by Gram-negative bacteria isolated from a sterile site, or nonsterile site in the setting of clinical infection.ResultsA total of 381 episodes of infection with GNB in 242 immunocompromised pediatric patients were identified. The mean age was 7.7 years. The most common pathogens were Enterobacterales followed by Pseudomonas and Acinetobacter spp. MDR GNB infections predominated causing 72% of the episodes, with alarming MDR rates among Escherichia coli (95.7%) and Klebsiella pneumoniae (82.7%). The overall rate of MDR GNB isolated increased from 62.7% in 2015 to 90% in 2017. Thrombocytopenia, chemotherapy and previous colonization or infection with the same organism during the past 12 months were found to be independent risk factors for infection with MDR GNB.ConclusionThis study provides data on the epidemiology of infections with MDR GNB in immunocompromised pediatric patients and illustrates the alarmingly high prevalence of these infections. This necessitates the frequent revisiting of treatment guidelines in these high-risk patients and the implementation of judicious antimicrobial stewardship programs and infection control policies to stabilize or decrease the prevalence of these infections.